A SWOT Analysis to Determine Strategies of Public Information Disclosure Quality Improvement - Irsyadinnas Irsyadinnas; Sinta Ningrum; Centurion Chandratama Priyatna (International Journal Labs, 2023)
This study aims to formulate alternative strategies in order to improve the quality of public information disclosure (KIP) in East Belitung Regency. The research method uses a descriptive qualitative approach. The data collection method is an interview with 2 main information and documentation management officials (PPID), and 8 auxiliary PPID. The selection of the ten respondents was carried out by purpossive sampling method. The interview results were analyzed using the SWOT analysis method. The results showed that a comprehensive strategy is needed to improve the quality of KIP implementation in East Belitung Regency through optimizing the use of strength and opportunity factors, as well as minimizing the weaknesses and threats faced by public bodies, especially from the institutional aspects of PPID, strengthening technical regulations, and variations in the use of public information dissemination media in East Belitung Regency.